Design Character Education Curriculum in Modern Pesantren Darussalam Gontor to Strengthening the Profile of Santri in Facing the VUCA Era - Rosendah Dwi Maulaya; Annisa Avilya; Syafa'atun Nur Inayah; Fasya Asy Shyifaauzzahra; Sitti Fadhilah Yasmin; Fera Favirotus Siyam (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
VUCA (Volatile, Uncertain, Complex, and Ambigue) is an acronym often used to describe the current state of the world. The world is developing. Technology is the participant that makes the greatest contribution to the development of the world. Technology provides convenience on the one hand but also raises new problems. Big Data, the Internet of Things (IoT), and Artificial Intelligence (AI) are extraordinary inventions that can provide easier, more effective, and more efficient life experiences. However, it also kills other areas of life, such as economics, sociology, and education. Humans will continue to compete to maintain their lives. This study aims to analyze the design of character education in modern pesantren to face the VUCA Era. The research methods used are library research and unstructured observation. Modern pesantren turn out to have complex character-strengthening education. The dynamics of student activities, from waking up to sleeping again, are unwittingly full of values. Education is not only inside the classroom but also outside the classroom. Modern pesantren are miniatures of people's lives. The students not only learn religious knowledge but also learn to live. Qualified individuals are needed to face the VUCA era and have resilience to rapid world changes. It is no exaggeration to say that pesantren education can produce quality output with these qualifications. Because modern pesantren educate life. What is educated is his discipline, his responsibilities, his qualifications, his competence, and his integrity.